Legal protection of customer data in implementing the financial information access law for tax purposes - Haryandu, Randu; Azheri, Busyra; Rembrandt, Rembrandt (Universitas Wiralodra, 2023)
The enactment of the Law on Access to Financial Information for Tax Purposes (Access to Financial Information) created a new paradigm in applying the principle of bank secrecy. The Law on Access to financial information has given authority to the Director General of Taxes to open taxpayer data at a bank even though the taxpayer is not being audited, billed, and investigated for tax crimes. This causes taxpayer data to be accessible at the bank if it meets predetermined criteria. The state must provide legal protection to secure bank customer data, so irresponsible parties do not misuse it. This study aims to determine and analyze the form of legal protection for customer data in implementing the Financial Information Access Law. This research method uses a normative juridical approach, analyzed normatively and qualitatively. The research results show that the Law on Access to Financial Information does not explicitly regulate the legal protection of customer data, and there are no administrative and criminal sanctions for parties who misuse customer data. Protection of customer data in implementing access to financial information is only found in the Regulation of the Minister of Finance. This Regulation of the Minister of Finance should regulate the technical implementation of the law. In the future, the government can conduct studies and change the Financial Information Access Law to guarantee legal protection for customer data regulated by law.